(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study was undertaken to analyze the effects of Swiss ball training with Plyometric circuit training on serve ability among men badminton players. The investigator has selected N=48 men inter collegiate levelstate level participated badminton players at random from various college of the Guntur district of Andhra Pradesh, India and their age range from eighteen to twenty five years as per their college record. The badminton players chosen for the study were divided into four equal groups n=12 and designated as experimental group ‘A’ experimental group ‘B’ experimental group ‘C’ and control group ‘D’. Swiss ball exercises training were given to group ‘A’ plyometric circuit training were given to group ‘B’, Combined training of Swiss ball exercises and plyometric circuit training were given to group ‘C’ and the ‘CG’ control group ‘D’ were restricted to participate in any activities. The trainings were given for a period of twelve weeks. The data were collected before and after the training by conducting French Stalter badminton serve test. The obtained data’s were analyzed by Analysis of Covariance (ANCOVA). The level of significant was fixed at 0.05 levels. The results of the study showed that Swiss ball exercises, plyometric circuit training and combined training significantly improved serve ability performance of the badminton players when comparative with control group. The Combined training group badminton players shown excellent performance in French Stalter badminton serve test when comparison with Swiss ball exercises group and plyometric circuit training group badminton players.